External Radiation Dose to the Shore Crab of Chinnavilai, a High Background Natural Radiation Area - Merit, Y. Anita; Smith, V. Robin Perinba (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The aim of the study was to determine the activity concentration and radiation dose of radionuclides 226Ra, 228Ra & 40K in shore crab Hemigrapsus Sanguineus, in Chinnavilai, Kayakumari district, Tamil Nadu, India. Gamma spectrometry is used for determine activity concentration and radiation dose of radionuclides (226Ra, 228Ra & 40K.). The total dose values due to both internal and external contributions by all three studied radionuclides fell between 26.51 and 53.19 µGy/day. These values are far below the dose limits (10 mGy/day) prescribed for aquatic animals by the US Department of Energy (2002) and hence the animals are safe, radiologically as far as these radionuclides are concerned. The minimum internal dose for 228Ra in shore crab 0.30 and the external dose 16.42. The total dose for 228Ra in shore crab 16.72. The maximum internal dose for 228Ra in shore crab 0.64 and the external dose 30.03. The total dose for 228Ra in shore crab 30.67.